2011
DOI: 10.1186/1756-3305-4-199
|View full text |Cite
|
Sign up to set email alerts
|

Giardia duodenalis assemblages and Entamoeba species infecting non-human primates in an Italian zoological garden: zoonotic potential and management traits

Abstract: BackgroundGiardia duodenalis and Entamoeba spp. are among the most common intestinal human protozoan parasites worldwide and they are frequently reported in captive non-human primates (NHP). From a public health point of view, infected animals in zoos constitute a risk for animal caretakers and visitors. In this study we carried out the molecular identification of G. duodenalis and Entamoeba spp. from nine species of primates housed in the zoological garden of Rome, to better ascertain their occurrence and zoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
36
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 33 publications
7
36
1
5
Order By: Relevance
“…A study conducted on primates housed in Rome Biopark revealed worrying levels of Giardia spp. infection in Ring Tailed Lemurs (81.2%), obtaining similar results to previous researches carried out in other parts of Europe and to those of the present work (Berrilli et al 2011;Levecke 2010;Levecke et al 2007). Those protozoa, along with Entamoeba spp.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…A study conducted on primates housed in Rome Biopark revealed worrying levels of Giardia spp. infection in Ring Tailed Lemurs (81.2%), obtaining similar results to previous researches carried out in other parts of Europe and to those of the present work (Berrilli et al 2011;Levecke 2010;Levecke et al 2007). Those protozoa, along with Entamoeba spp.…”
Section: Discussionsupporting
confidence: 81%
“…appear very difficult to control and they are resistant to repeated treatments; for example, the veterinarians of the bio-park in Rome have unsuccessfully tried to eradicate Giardia spp. from a colony of ring-tailed lemurs through many specific treatments (Berrilli et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, many of the parasites commonly found in zoological gardens are responsible for zoonoses, thus representing a potential public health problem (Klaus et al, 2000;Berrilli et al, 2011). Among these, nematodes of the genus Trichuris known as whipworms are recognized to infect several mammalian species, including humans (Reichard et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have reported the possibility that these protozoa may be transmitted to humans or other animals (RAJAH SALIM et al, 1999). Transmission between animals and humans in association with clinical outbreaks among animal keepers has been reported in various studies (MILLER et al, 2004;LEVECKE et al, 2007;BERRILLI et al, 2011). The presence of zoonotic parasites emphasizes the need to use rapid copro-microscopic techniques and specific devices that protect the operator.…”
Section: Discussionmentioning
confidence: 99%